Compliance and truthfulness: leveraging peer information with competitive audit mechanisms - Goeschl, Timo; Oestreich, Marcel; Soldà, Alice (Journal of the Association of Environmental and Resource Economists, 2023)
How to design audit mechanisms that harness the benefits of self-reporting for achieving compliance with regulatory targets while limiting misreporting is a pressing question in many regulatory contexts, from climate policies to public health. Contrasting random audit and competitive audit mechanisms, this study theoretically and experimentally examines their performance in regulating socially undesirable emissions when peer information about others’ emissions is present or absent. Our focus is on the compliance of emission levels with regulatory targets, going beyond existing results on truthfulness of reporting. Confirming theoretical predictions, the experiment shows that in contrast to the random audit mechanism, the competitive audit mechanism can leverage peer information for compliance: emission levels are closer to the social optimum. Yet, emission levels fall somewhat short of full compliance. The results highlight the considerable potential of competitive audit mechanisms for achieving not only more truthfulness but also more compliance.